2019
DOI: 10.3390/agriculture9070141
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of a Low-Cost Capacitive Moisture Sensor to Integrate the Automated Soil Moisture Monitoring System

Abstract: Readily available moisture in the root zone is very important for optimum plant growth. The available techniques to determine soil moisture content have practical limitations owing to their high cost, dependence on labor, and time consumption. We have developed a prototype for automated soil moisture monitoring using a low-cost capacitive soil moisture sensor (SKU:SEN0193) for data acquisition, connected to the internet. A soil-specific calibration was performed to integrate the sensor with the automated soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 26 publications
2
46
0
1
Order By: Relevance
“…The characterization of capacitance-type soil moisture sensors in laboratory conditions has produced highly repetitive readings among sensors [ 21 , 43 ]. Nevertheless, in field conditions, large differences in sensor measurements have been reported by many authors [ 26 , 60 , 61 , 62 , 63 ]. Our results show large sensor-to-sensor differences, even though repeated sensors were installed precisely at the same soil locations in terms of depth and position relative to the dripper.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of capacitance-type soil moisture sensors in laboratory conditions has produced highly repetitive readings among sensors [ 21 , 43 ]. Nevertheless, in field conditions, large differences in sensor measurements have been reported by many authors [ 26 , 60 , 61 , 62 , 63 ]. Our results show large sensor-to-sensor differences, even though repeated sensors were installed precisely at the same soil locations in terms of depth and position relative to the dripper.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is useful to investigate its performance and understand its limits both for irrigation management and for soil moisture determination, e.g., in geotechnical applications. To the best of our knowledge, the sensor studied in the present paper has been characterized only once before [32], when it as evaluated for accuracy and reliability under laboratory conditions. The authors found that this sensor did not perform acceptably in predicting soil moisture content in a laboratory soil mixture prepared by mixing organic-rich soil and vermiculite, while it can estimate soil water in gardening soil in the so-called "field capacity" range.…”
Section: Introductionmentioning
confidence: 99%
“…As such, soil sensors that focus on low-cost capacitive sensing techniques were developed [22,31]. Such sensors were still bulky and inorganic; on the other hand, other researchers were working on a battery-free, wireless solution to soil-monitoring sensors that harvests the energy from temperature fluctuation [18].…”
Section: Related Work Hci For Farming and Human-nature Interactionmentioning
confidence: 99%
“…Bringing state-of-the-art sensors, actuators, and interactive devices outdoors and into the wild (e.g., farmland [31], forests [37], and wetland [8]) raises new challenges, such as effectively deploying such devices on a large scale and creating ubiquitous computing that can weave itself into nature seamlessly [45]. Existing works show that the deployment of sensors and other functional devices over large distributed areas is non-trivial [21], especially when these areas are remote and hard to reach.…”
Section: Introductionmentioning
confidence: 99%